The Role of Mindfulness and Self Compassion toward Depression among Pregnant Women - Endang Fourianalistyawati; Aisyah Uswatunnisa; Alfira Chairunnisa (Intelektual Pustaka Media Utama, 2018)
Pregnant women tend to experience depression during pregnancy. This can affect mothers and babies’ health widely. Previous research has found that mindfulness and self-compassion can reduce depression in pregnant women in abroad, but it still no specific research on it in Indonesia. Therefore, the purpose of this study was to see the relationship and also the role of mindfulness and self-compassion toward depression in pregnant women. Participants in this study were 121 pregnant women who lived in the area of Jakarta, Bogor, Depok, Tangerang, and Bekasi. This study used Five Facets of Mindfulness Questionnaire (FFMQ) to measure mindfulness, Self-Compassion Scale (SCS) to measure self-compassion, and Postnatal Depression Scale (EPDS) to measure depression in pregnant women. The results of this study showed that three dimensions of mindfulness (describing, acting with awareness, and non-judging) and self-compassion as a whole had a significant relationship with depression. Then the results of multiple regression tests conducted to get results that describing dimensions of mindfulness and self-compassion have a role to depression in pregnant women.